BOOK ANNOUNCEMENTS - "TO TAKE NOTE OF" - J.A, van den Berg (Acta Theologica)
Colleauges from the four departments from the Faculty of Theology and Religion at the Unviersity of the Free State have indicated important recent publications to take note of.